Antimicrobial cryogel dressings towards effective wound healing - Akin, Basak; Ozmen, Mehmet Murat (OICC Press, 2022)
Cryogels are macroporous hydrogels that have been widely utilized in a variety of biomedical applications including wound dressings. Cryogels reveal superior mechanical and swelling properties as well as large and interconnected porosity. As traditional hydrogel wound dressings generally show undesirable mechanical and swelling characteristics, cryogels, due to their toughness and superfast swelling, offer an outstanding platform to address the growing number of various types of wounds. Moreover, recently, cryogel wound dressings loaded with an antimicrobial agent emerged as a feasible option to reduce infection, and thus improve the wound healing process. However, a comprehensive review of antimicrobial cryogels as a wound dressing is still lacking in the literature. In this review, we summarize the progress of cryogels in the area of wound dressings and provide an overview of the various polymers, namely, natural and synthetic which have been employed in cryogel wound dressing preparation. Furthermore, the most prominent antimicrobial agents incorporated in cryogel wound dressings are provided. Finally, the future directions of cryogel wound dressings for wound healing are also discussed.
Keywords: Antimicrobial; Biomaterial; Cryogel; Macroporous; Wound dressing; SILK FIBROIN; SCAFFOLDS; HYDROGELS; FABRICATION; HEMORRHAGE; DELIVERY; RELEASE; PHEMA; Engineering; Materials Science